Strategi Public Relations dan Press Release: Studi Pada Karyawan PLN (Perusahaan Listrik Negara) - Vita Mayastinasari; Ilham Prisgunanto (Prisani Cendekia, 2025)
Disputes with the media frequently arise during the State Electricity Company’s field operations. It is acknowledged that a strategic approach is necessary in crafting and designing messages and narratives that align with the public’s perception of the company’s image. This community service initiative aims to provide specialized training on understanding the digital landscape and effectively packaging messages and narratives for the public. This article reports on a community service initiative for PLN to select effective strategies and tactics for crafting messages. The initiative involved conducting workshops and focus group discussions (FGDs) with PLN staff to provide guidance to field personnel. It also addressed the legal framework for resolving disputes with the media and digital content creators. Many PLN field staff lack a clear understanding of the Press Law and the Law on Information and Electronic Transactions. A comprehensive strategy was developed using the STOP SIT model (Segmentation, Targeting, Objectives, Positioning, Sequence of Tools, Integration, and Time Scales), ensuring that the design of the narrative is more specific and effective.